A meta-analysis of the financial performance of family firms: Another attempt. Issue 1 (March 2015) - Wagner, Dominik; Block, Joern H.; Miller, Danny; Schwens, Christian; Xi, Guoqian
Highlights The study presents the results of a comprehensive meta-analysis of the financial performance of family firms. Family firms show superior performance compared to non-family firms. We find moderating factors on country, firm, and family levels.